A high-resolution multiband survey of Westerlund 2 with the Hubble space telescope: III. The present-day stellar mass function - Zeidler, Peter; Grebel, Eva K.; Pasquali, Anna (Arxiv, 2017)
We present a detailed analysis of the spatial distribution of the stellar population and the present-day mass function (PDMF) of the Westerlund 2 (Wd2) region using the data from our high resolution multi-band survey with the Hubble Space Telescope. We used state-of-the-art artificial star tests to determine spatially resolved completeness maps for each of the broad-band filters. We reach a level of completeness of 50 % down to F555W=24.8 mag (0.7 $M_\odot$) and F814W=23.3 mag (0.2 $M_\odot$) in the optical and F125W=20.2 mag and F160W=19.4 mag (both 0.12 $M_\odot$) in the infrared throughout the field of view. We had previously reported that the core of Wd2 consists of two clumps: namely the main cluster (MC) and the northern clump (NC). From the spatial distribution of the completeness corrected population, we find that their stellar surface densities are 1114 stars pc$^{-2}$ and 555 stars pc$^{-2}$, respectively, down to F814W=21.8 mag. We find that the present-day mass function (PDMF) of Wd2 has a slope of $Γ=-1.46 ± 0.06$, which translates to a total stellar cluster mass of $(3.6 ± 0.3) · 10^4 M_\odot$. The spatial analysis of the PDMF reveals that the cluster population is mass-segregated, most likely primordial. In addition, we report the detection of a stellar population of spatially uniformly distributed low-mass (<0.15 $M_\odot$) stars, extending into the gas ridges of the surrounding gas and dust cloud, as well as a confined region of reddened stars, likely caused by a foreground CO cloud. We find hints that a cloud-cloud collision might be the origin of the formation of Wd2.
Gesehen am 24.10.2017